The Relationship Between the Quality of Academic Services and Learning Facilities and Students’ Satisfaction - Suprianto, Hendra; Ahyani, Nur; Kesumawati, Nila (PPSDP International Journal of Education, 2025)
Higher education as one of the service providers in the field of education must be able to provide and create student satisfaction. Student satisfaction can be generated from the quality of services provided and the learning facilities provided which are directly related to the student teaching and learning process. This study applies a non-parametric statistical method through the analysis of the relationship with the spearman rank and the multivariate spearman rank which aims to examine whether the quality of academic services and learning facilities has a significant relationship either partially or jointly with student satisfaction at the Institute of Health Sciences and Technology Muhammadiyah Palembang. The population in this study is active students in the 2023/2024 academic year with a total of 1,530 people, and the number of samples taken is 153 students. Tools to collect data information using questionnaires that utilize the Likert scale. The results of the study showed that (1) the quality of academic services has a significant relationship with learning facilities and vice versa, (2) the quality of academic services has a significant relationship with student satisfaction, (3) learning facilities have a significant relationship with student satisfaction, (4) the quality of academic services and learning facilities together have a significant relationship with student satisfaction with a value of R2=0.868 with percent of 86.8%.